2016
DOI: 10.1051/matecconf/20166702005
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted Synthesis of Hierarchical ZnO Nanostructures and Their Photocatalytic Properties

Abstract: Abstract. Hierarchical ZnO nanostructures were fabricated via a rapid and facile microwave-assisted route with different zinc salts as reactants. The obtained hierarchical ZnO nanostructures have good crystallinity and high purity. Moreover, it was found that various zinc salts have an obvious effect on the morphologies and microstructures of the final products. Additionally, the photocatalytic activity of the obtained ZnO samples under visible-light irradiation was also evaluated by degradation of Rhodamine B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(33 reference statements)
0
2
0
Order By: Relevance
“… Examples of various ZnO structures obtained by the microwave hydrothermal synthesis: ( a , b ) SEM and TEM images of N-ZnO microflowers (Reprinted with permission from [ 615 ], Copyright ©2016 Ou et al, Article licensed under a CC BY 4.0, ); ( c ) SEM image of ZnO bihexagonal rod-like (Reprinted with permission from [ 581 ], Copyright ©2013 Barreto et al, Article licensed under a CC BY 3.0, ); ( d ) TEM image of Cd doped ZnO/CNT carbon nanotubes nanocomposites (Reprinted from [ 698 ], Copyright 2017 The Authors, with permission from Elsevier [OR APPLICABLE SOCIETY COPYRIGHT OWNER]. Article licensed under a CC BY-NC-ND 4.0, .…”
Section: Figurementioning
confidence: 99%
“… Examples of various ZnO structures obtained by the microwave hydrothermal synthesis: ( a , b ) SEM and TEM images of N-ZnO microflowers (Reprinted with permission from [ 615 ], Copyright ©2016 Ou et al, Article licensed under a CC BY 4.0, ); ( c ) SEM image of ZnO bihexagonal rod-like (Reprinted with permission from [ 581 ], Copyright ©2013 Barreto et al, Article licensed under a CC BY 3.0, ); ( d ) TEM image of Cd doped ZnO/CNT carbon nanotubes nanocomposites (Reprinted from [ 698 ], Copyright 2017 The Authors, with permission from Elsevier [OR APPLICABLE SOCIETY COPYRIGHT OWNER]. Article licensed under a CC BY-NC-ND 4.0, .…”
Section: Figurementioning
confidence: 99%
“…So far, several dyes and organic pollutants have been studied for its photoelectrocatalytic degradation using ZnO nanostructures. Some of them are rodhamine B [119][120][121][122][123] methyl orange [71,[124][125][126], methylene blue [88,124,[127][128][129][130][131][132][133][134], congo red [133,135], resazurin [136], thiacloprid [137] and roxarsone [138]. It has been reported that differences in surface characteristics such as morphology and defects influenced photoelectrocatalytic degradation efficiency.…”
Section: Photodegradation Of Organic Pollutantsmentioning
confidence: 99%